Experimental study on seismic performance of a novel splice joint in hybrid concrete-steel structures - Ma, Xiaotong; Wang, Jinyu; Guo, Tianxiang; Bao, Chao; Cao, Fusheng (Frontiers in Materials, 2025)
The revitalization of aging urban districts can be significantly advanced through the redevelopment of existing buildings using hybrid concrete-steel structures with added stories. The connection between the newly integrated steel structure at the upper portion and the existing concrete structure at the lower portion performs a critical function in ensuring the safety and stability of hybrid concrete-steel systems. To enhance the strength and seismic resilience of the joints in these hybrid structures, this study presents a novel splice joint incorporating Engineered Cementitious Composites (ECC) concrete. A quasi-static testing method was employed to compare and analyze the failure characteristics, rotational behavior between beams and columns, hysteretic response, and skeleton curves of the proposed ECC-based splice joints and conventional concrete joints. The results reveal that the inclusion of ECC concrete significantly enhances the bonding strength at the secondary casting interface, thereby shifting the failure mode from the interface to plastic deformations at the beam ends. Furthermore, the hybrid joints demonstrated a 33% increase in the horizontal displacement threshold and an 18% improvement in load-bearing capacity, effectively limiting upper structure rotation and minimizing deformation. These findings validate the effectiveness of the proposed splice joint in enhancing the seismic behavior of hybrid concrete-steel joints. These findings highlight the enhanced seismic performance of hybrid concrete-steel structure joints and provide valuable insights for the design of lightweight steel-frame structures with added stories.